PERAN BADAN KESATUAN BANGSA DAN POLITIK KOTA PALANGKA RAYA DALAM PENYELENGGARAAN PENDIDIKAN POLITIK BAGI PEMILIH PEMULA DI TAHUN 2024 - angelia, novita mayasari (JURNAL PEMERINTAHAN, POLITIK ANGGARAN DAN ADIMINSTRASI PUBLIK, 2024)
In the 2019 election, data on voter participation in Palangka Raya was 83,7%. It exceeded the central KPU target of 77.5%. This increase in voter participation is influenced by various aspects. Both socialization was carried out by various institutions and through social media. Therefore, it is an essential task for various related institutions, one of which is the National Unity and Politics Agency of Palangka Raya City, to carry out massive outreach to novice voters in Palangka Raya City through organizing political education facing the 2024 elections which aims to highlight the importance of participating in the general election to determine the future of the country in the next five years. This research aims to determine the extent of the role of the National Unity and Politics Agency in implementing Political Education for beginner voters in the City of Palangka Raya, as well as measuring the extent to which the program results of the National Unity and Politics Agency of Palangka Raya City have been achieved in providing Political Education for beginner voters. The research was carried out through observation, interviews, and documentation studies with research subjects. It used qualitative descriptive techniques, where the researcher tried to describe and explain the contents of the work program for organizing political education implemented by the Palangka Raya City National and Political Unity Agency.